Prototype of an Expert System for the Selection of Aircraft Structural Materials - Xuelong Hao; Chen Wen; Ning Zhao; Lu Lu; Kai Zhang; Donghui Zhang (International Journal of Photoenergy)
Expert systems (ES) are widely used for engineering and manufacturing applications nowadays. In order to solve the problems in material selection in the aviation field, an aircraft material expert system (AMES) was developed. This expert system is based on the knowledge of multiple experts and aviation data. A decision support system (DSS) was designed for selecting the materials used in aviation fields. The flows of material selection were designed, and the models of AMES were established. A data base system was also designed to implement AMES.